The Current Lipid Guidelines for Prevention of Cardiovascular Diseases - A Santoso (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Guidelines on lipid-lowering treatment for prevention of CVD (cardiovascular diseases) .....